Guest Editors: Dakwah, Islamic Management And Contemporary Issues - Mohd Rosmizi Abd Rahman; Abdul Rahim Zumrah; Suhailiza Md. Hamdani; Khadijah Muda (Universiti Sains Islam Malaysia, 2024)
This special issue brings together thirteen selected articles of which nine of them were presented at International Conference on Da'wah and Islamic Management (IC-DAIM 2017) which was held on 31 October to 1 November 2017. The conference was organized by Dakwah and Islamic Management Program, Faculty of Leadership and Management, Universiti Sains Islam Malaysia (USIM).